Review of Salles, R.; Molina Ayala, J. Alejandro de Afrodisia. De la mixtura y el crecimiento (2019) - Valencia Constantino, Genaro (Revista Archai, 2020)
Review of Salles, R.; Molina Ayala, J. Alejandro de Afrodisia. De la mixtura y el crecimiento (2019).